ANALISIS PENGARUH SIFAT MACHIAVELLIANISME¸ ETIKA DAN TANGGUNG JAWAB SOSIAL, FAKTOR SITUASIONAL DAN LOCUS OF CONTROL TERHADAP PENGAMBILAN KEPUTUSAN ETIS OLEH KONSULTAN PAJAK - Agung Tofiq, Tri; Dwi Mulyani, Susi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2018)
The following research aimed to study the effect of Machiavellian personality, Perceived Role of Ethics, and Social Responsibility (PRESOR), situational factor, and both internal and external Locus of control on ethical decision making made by tax consultant registered in Indonesian Tax Consultants Associations for Banten Region. The data is gathered using questionnaire for tax consultant registered in Indonesian Tax Consultants Associations for Banten Region. There are four independent variable with Likert scale used on this research i.e. of Machiavellian personality, Perceived Role of Ethics, and Social Responsibility (PRESOR), situational factor, and both internal and external Locus of control; and ethical decision making as the dependent variable with nominal scale. These data is analyzed with logistic regression using SPSS version 15.0. The research shows that: 1) Machiavellian personality doesn’t have significant effect on tax consultant’s ethical decision making, 2) Perceived Role of Ethics and Social Responsibility (PRESOR) positively affect tax consultant’s ethical decision making significantly, 3) Situational factors positively affect tax consultant’s ethical decision making significantly, 4) Internal and External Locus of control positively affect tax consultant’s ethical decision making significantly. Simultaneous testing shows that Machiavellian personality, Perceived Role of Ethics, and Social Responsibility (PRESOR), situational factor, and both internal and external Locus of control have significant effect on ethical decision making made by tax consultant as big as 68,60%